Cities' Identity Through Architecture and Arts Proceedings of the 1st International Conference on Cities' Identitiy through Architecture & Arts, Cairo, Egypt, 11-13 May 2017 - Versaci, Antonella; Nour, Zeinab; Hawkes, Dean; Bougdah, Hocine; Ghoneem, Mahmoud; Catalani, Anna; Trapani, Ferdinando; SotocaI, Adolf (Taylor & Francis, 2018)
This book is a combination of innovative research submitted to a conference on Cities' Identity Through Architecture and Arts (CITAA) whereas scholars from all over the world gather in one venue to discuss cultural, historical, and economic issues of the city. Thus, the book offers a collective and global solution that is applicable on a universal level. The research presented in this book was conducted by authors, or rather participants of the conference from, three different continents of the world and organized by IEREK. It was a distinct opportunity for them to share their thoughts with leading scholars and professionals in the field of Architecture, Arts, and Planning. The research and materials in this book are directed at those who are actively engaged in the decision-making processes and to a heterogeneous audience who has an interest to critically examine all the new literature available in the field. A special word of thanks should be made to the editors of this book and to all the authors and co-authors of the chapters who collectively provided the academic community with unique and increasingly valuable literature.